Zaburzenia neurologopedyczne i neurorozwojowe w dyskraniach syndromicznych na przykładzie zespołu Aperta. Przegląd literatury i opis trzech przypadków - Hankus, Agnieszka (Logopedia Silesiana, 2014)
Neurologopedical and neurodevelopmental disorders in syndromic dyscranias on the In this article the authors present one of the most frequent clinical syndroms connected with complex dyscranias – the acroce phalosyndactylia of A type, i.e. Apert syndrom. Authors present cases of three children touched by this illness and they will show the disorders of cognitive and communicative functions that aresignificant as regards the work of speech neurotherapist. possibility to communicate.